EFECTIVINESS ON TRAINING PROGRAM OF INTEGRATING CHARACTER EDUCATION IN LEARNING AT MGMP PKn SMP IN TAPIN - Fatimah . (LPPM Universitas Negeri Jakarta, 2017)
The main goal of this research is to analyzed the efectiviness of the implementation of on training program integrating character education in the learning of Civic Education for the learning teacher community of civics education subyect of yunior high school in Tapin district. The research in evaluative research by using an evaluation model in mesuare the efectiviness of the program Kirkpartrick. Data are collected techniques using Qualitative approach with technichques observation, interviews, and documentation., also questionerres. The reactions showed a high level of response categories and efective, learning level is efective, level behavioral is efective and very useful, because it change behavior in teachers attitude, skill and knawledge, and resuls level showed a responsibility of civics education teachers giving positive response as seen from their working effectiveness as the manifestation of qualities of working and creativity.